(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
Calculation results scattering of plane electromagnetic waves on a parabolic and plane lattices of dielectric resonators in the open space were presented. Every resonator of lattice excited on main azimuthally symmetric oscillation of it lowest magnetic mode. Common pattern of spatial distribution scattering field in the short-distance zone has been examined. It’s showing to a possibility of field increasing in the lattice focuses area.